Utilization of fermented soybeans paste as flavoring lamination for Turkish dry-cured meat. (May 2017) - Ahhmed, Abdulatef; Özcan, Ceyda; Karaman, Safa; Öztürk, İsmet; Çam, Mustafa; Fayemi, Peter O.; Kaneko, Gen; Muguruma, Michio; Sakata, Ryoichi; Yetim, Hasan
Abstract: The effects of utilizing fermented soybeans paste (miso) as an alternative flavor-coating material for eliminating unpleasant odor of sulphuric and sotolone compounds from cemen in commercial pastirma were investigated. Results showed that miso-pastirma (MP) and commercial pastirma (CP) had higher L* values in comparison with the fresh meat. While no pathogen was detected in all the meat samples, statistically significant stearic acid was increased (P < 0.05) and also oleic and arachidic acids were observed in MP. SDS-PAGE patterns indicated that miso had higher impacts on muscle proteins than cemen suggesting that miso can generate proteins and peptides with better technological or nutritional properties. None of the sulphur containing compounds responsible for unpleasant odor was detected in MP. Limonene, 5 esters, beta-pinene and saponins in MP contributed to citrus fruit aroma with smoother, roasty flavor and delicious taste. These findings suggest that miso contain good flavoring molecules for enhancing fruity smell and quality of pastirma. Thus, laminating cured meat with miso can be used as an alternative to cemen for producing healthier pastirma with extended shelf life and better flavor.